2019
DOI: 10.1123/jsm.2018-0261
|View full text |Cite
|
Sign up to set email alerts
|

Running Recession: A Trend Analysis of Running Involvement and Runner Characteristics to Understand Declining Participation

Abstract: Market trends indicate the distance running event industry is facing a running recession. Since 2013, consumer demand has declined annually while supply increased. The current research provides insight into why running as a recreational activity is declining and implications for organized events’ utility. Based on seven years of participants’ postevent surveys from a long-distance running event, the value placed on hedonic, symbolic, and lifestyle features of running (i.e., running involvement) is gradually de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 68 publications
0
6
0
2
Order By: Relevance
“…Thus, the generalisation of the results must require some level of caution. Second, the findings were limited in terms of causal inference because of the cross-sectional research design (Kennedy et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Thus, the generalisation of the results must require some level of caution. Second, the findings were limited in terms of causal inference because of the cross-sectional research design (Kennedy et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Last, by using interdependent happiness as a dependent variable, the three factors of involvement as independent variables, and age and marital status as control variables, multiple regression analyses were conducted for each of the four groups. Although consensus on the effects of demographic variables on involvement has not yet emerged (Kennedy et al, 2019), some research reported negative and positive relationships regarding age (e.g. Havitz, Kaczynski, & Mannell, 2013) and marriage (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…El sector deportivo ha experimentado una evolución muy importante en los últimos años a nivel nacional, desde el tipo de actividades practicadas hasta factores que tienen influencia sobre la economía (1). En particular, la participación en eventos deportivos se ha convertido en una de las actividades de ocio activo más populares de la población en los últimos años (2,3). En España se ha producido un crecimiento notable del número de eventos deportivos principalmente en el ámbito no profesional que se celebran tanto a nivel local, como autonómico, nacional e internacional (4).…”
Section: Introductionunclassified